2004
DOI: 10.1023/b:bile.0000045642.19299.3f
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterisation of an alkaline protease used in tannery industry from Bacillus licheniformis

Abstract: An extracellular alkaline protease produced by Bacillus licheniformis AP-1 was purified 76-fold, yielding a single 28 kDa band on SDS-PAGE. It was optimally active at pH 11 and at 60 degrees C (assayed over 10 min). The protease was completely inhibited by phenylmethylsulfonyl fluoride and diodopropyl fluorophosphate, with little increase upon Ca2+ and Mg2+ addition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 9 publications
3
15
0
Order By: Relevance
“…The enzyme was completely inhibited by 1 mM DFP, a well-known inhibitor of serine protease 4,21 suggesting that this enzyme was a serine protease. Similar results of serine proteases completely inhibited by DFP were observed in serine protease produced by B. licheniformis 22 , B. pumilus 7,21 and B. intermedius 3-19 23 . the enzyme under denaturing condition was estimated to be 27 kDa, similar to the molecular masses of alkaline proteases, which were in the ranges of 15 to 30 kDa 11 .…”
Section: Inhibitors Of the Protease Inhibitors Of The Protease Inhibisupporting
confidence: 80%
“…The enzyme was completely inhibited by 1 mM DFP, a well-known inhibitor of serine protease 4,21 suggesting that this enzyme was a serine protease. Similar results of serine proteases completely inhibited by DFP were observed in serine protease produced by B. licheniformis 22 , B. pumilus 7,21 and B. intermedius 3-19 23 . the enzyme under denaturing condition was estimated to be 27 kDa, similar to the molecular masses of alkaline proteases, which were in the ranges of 15 to 30 kDa 11 .…”
Section: Inhibitors Of the Protease Inhibitors Of The Protease Inhibisupporting
confidence: 80%
“…The ability of strain AK-R to grow over a wide range of NaCl concentrations (up to 25%), with maximum cells growth at 2.5-5% NaCl, indicated the halo-tolerance nature of this organism (JAIN et al, 2012). Studies on the effect of salinity on growth of halotolerant bacteria have shown a change in the polar lipid composition of the cell membranes and an increased salt concentration creates change in the lipid resulting in decrease of growth rate causing reduced enzyme production (TANG, X. M. et al, 2004). Strain AK-R and its extracellular alkaline protease with salt tolerance signify their potential application in laundry industry (HADDAR et al, 2009b).…”
Section: Effect Of Salinitymentioning
confidence: 99%
“…These cations probably protect the enzyme against thermal denaturation and therefore maintain the active conformation of the enzyme at high temperature (CHU, 2007). In addition; the inhibitory effect of other ions on alkaline protease is mostly attributed to metal catalyzed oxidation of amino acid residues essential to the enzyme activity (TANG et al, 2004). …”
Section: Effect Of Various Metalsmentioning
confidence: 99%
“…For instance A. flavus, Aspergillus niger and Aspergillus fumigutus were reported to produce enzymes essential in tannery industry (Barthomeuf et al, 1994). Thanikaivelan et al (2004) reported the potential of Aspergillus tamarii in tannery biotechnology whereas Aspergillus terreus was reported to produce tannery enzyme for processing leather (Tang et al, 2004).…”
Section: Aspergillus In Industrial Applicationmentioning
confidence: 99%